ANALYSIS OF THE FINITE VERB PHRASES IN THE SHORT STORIES THE GIFT OF THE MAGI AND COSMOPOLITE IN A CAFÉ BY O. HENRY - Aulia, Rima Fitri; Suyudi, Ichwan (Journal of Language and Literature, 2019)
This research focused on finding the types of finite verb and main verbs. The researcher used the short stories The Gift of The Magi and Cosmopolite in a Café by O.Henry to limit the finding data. The method of this research is qualitative research. The result of this research showed that there are 361 finite verb phrases and divided into two types of finite verbs, 1. Main verbs stand alone which occur mostly with 65.93%, 2. Auxiliaries stand with the main verb with 34.07% which may be modal (29.27%), passive (18.70%), perfective (24.39%), progressive (6.50%), combination of two auxiliaries (12.20%), and the negative do- periphrasis auxiliary (8.94%). Based on 361 datas of finite verb phrases, the researcher found the most dominant type of main verb is action verb with 62.05% and stative verb with 37.95%.